Potential Immuno-modulatory activity of Probiotics containing Lactobacillusacidophilus and Lacobacilluscasei to increase the ratio of IFN γ/IL-4 in patients with Allergic Rhinitis (Bangladesh Journal of Medical Science, 2018)
Aims: This study aimed to determine the effect of probiotic combination on ratio of IFN-γ: IL-4 levels in patients with allergic rhinitis.Materials and methods: Single blind, randomized controlled trial.This study included 40 patients with severe allergic rhinitis according to WHO criteria. This study used 2 treatment groups with probiotics and placebo control group. IFN γ and IL-4 levels were evaluated using ELISA method. Data were analyzed using paired T test with 95% confidence intervalsResults and Discussion: In the treatment group, the levels of IFN-γ increased significantly (p